Role of Joshi's External Stabilization System Fixator in Proximal Humerus Fractures - Baskar Chockalingam (Journal of Orthopedics and Joint Surgery)
Background: Proximal humerus fracture (PHF) contributes 4–5% of fractures that are bimodal in distribution. The most common etiology includes accidental falls in elderly population and road traffic accident (RTA) in younger population. There is a wide range of treatments starting from conservative to advanced techniques like replacement. The outcome depends on various factors like mode of treatment, age of the patient, anatomy of fracture, and associated pathological conditions. In this study, we justify how Joshi's external stabilization system (JESS) method scores over other methods of fixation. Material and methods: This study includes 42 patients aged between 19 and 88, out of which 24 were females and 18 males. All surgeries were done between 2019 and 2022 under regional block. Fractures are classified according to Neer's classification. All patients were followed up regularly and assessment was done based on both functional and radiological improvement. Results: The total number of cases was 42. The number of patients aged above 45 years was 29 and <45 years were 13. Out of the 42 cases, 24 cases were due to RTA. Based on Neer's classification, Neer type I, II, IV, and head split cases were 13, 16, 11, and 2, respectively. The outcome was assessed based on constant score. Two cases progressed to nonunion and four cases underwent premature removal due to various reasons. Finally, 66% of the cases showed excellent outcomes. Discussion: Proximal humerus fractures (PHF) have always been a challenge for orthopedic surgeons and remain controversial. As we mentioned earlier here, one of the main factors deciding the outcome is mode of fixation. JESS has the advantage of rigid fixation, early mobilization, and no loosening. JESS stands superior to plating and K-wires in this aspect. Hence, JESS fixation in PHF is a wonderful and viable option for fixation method irrespective of the age and fracture pattern.